Successful management of a triplet heterotropic caesarean scar pregnancy in spontaneous conception - Yelurkar, Nilofar Imamhusen; Shah, Dharam Jatin; Satia, Meena Naresh; Badhwar, Vijaya Rajesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
A cesarean scar ectopic pregnancy -CSEP is a fairly uncommon presentation wherein the conceptus is implanted at the exact scar site of the previous cesarean section deep in the myometrium. Given the relatively rare incidence of CSEP establishing a diagnosis of CSEP can be challenging current standards of therapy have been derived from data obtained from a limited number of patient’s management options for CSEP range from medical line of treatment to surgical interventions such as sonography guided injections to laparoscopic excision or laparotomy or combination of these modalities. Herein we report a rare case of triplet pregnancy with one gestation sac implanted at the site of lower segment scar diagnosed on transvaginal ultrasonography along with MRI who was managed successfully with systemic methotrexate.